2012
DOI: 10.1682/jrrd.2011.09.0164
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sleep disturbances in posttraumatic stress disorder: A review

Abstract: Abstract-Sleep disturbances are among the most commonly reported posttraumatic stress disorder (PTSD) symptoms. It is essential to conduct a careful assessment of the presenting sleep disturbance to select the optimal available treatment. Cognitivebehavioral therapies (CBTs) are at least as effective as pharmacologic treatment in the short-term and more enduring in their beneficial effects. Cognitive-behavioral treatment for insomnia and imagery rehearsal therapy have been developed to specifically treat insom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(73 citation statements)
references
References 111 publications
0
71
0
Order By: Relevance
“…A recent meta-analysis demonstrated that IRT as compared to prazosin, an alpha-aderenergic blocker previously shown to be effective in reducing nightmares [64], produced equivalent reductions in nightmare frequency and associated sleep and trauma symptoms [67]. As such, the American Academy of Sleep Medicine and Veterans Administration/ Department of Defense endorses prazosin for the treatment of PTSD nightmares [64,68] which was further supported by two prazosin meta-analyses published in 2015 [69,70].…”
Section: Recent Treatment Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…A recent meta-analysis demonstrated that IRT as compared to prazosin, an alpha-aderenergic blocker previously shown to be effective in reducing nightmares [64], produced equivalent reductions in nightmare frequency and associated sleep and trauma symptoms [67]. As such, the American Academy of Sleep Medicine and Veterans Administration/ Department of Defense endorses prazosin for the treatment of PTSD nightmares [64,68] which was further supported by two prazosin meta-analyses published in 2015 [69,70].…”
Section: Recent Treatment Studiesmentioning
confidence: 91%
“…Like psychotherapy, treatment by SSRIs is associated with improved sleep quality [68]. Unfortunately, these medications also have sleep-related side effects, including insomnia and periodic limb movement sleep disorder [68].…”
Section: Recent Treatment Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of comorbid PTSD and TBI generally should follow the VA/DOD CPG for each condition, and following the steps mentioned earlier in order from 1 to 4 is recommended for most clinical situations. Additional recommended resources are companion articles in this issue by Gibson (PTSD and chronic pain) [77] and Schoenfeld et al (PTSD and insomnia) [78].…”
Section: General Principles For Managing Ptsd In Combat Veteran With Tbimentioning
confidence: 99%
“…Neurologic trauma such as Traumatic Brain Injury (TBI) can lead to decreased adherence to therapy as a result of cognitive dysfunction and poor motivation. All of the above conditions are inextricably linked to sleep disturbances which may increase the risk of nocturnal violence [4][5][6][7].…”
mentioning
confidence: 99%